The Effect of Peer Influence and Neighborhood Quality on Incarcerated Fathers’ Attachment - Tadros, Eman (International journal of offender therapy and comparative criminology, 2025)
Commonly referred to as the “hidden victims” of incarceration, children with a parent who is intermittently or repeatedly incarcerated face various challenges that exacerbate behavioral and psychological development. Using a baseline adaptation of the Multi-site Family Study on Incarceration, Parenting and Partnering (MFS-IP), we sought to clarify how peer influence and neighborhood quality can predict the extent of an incarcerated father’s attachment to the focal child and partner. Results showed a negative association between negative peer influence and poor neighborhood quality. Conversely, incarcerated fathers’ relationship with their biological mother and fathers produced a significant positive association. These findings propose that risk and protective factors can directly influence attachment levels with the focal child, as suggested by Social Control Theory. This article provides a basis for a more comprehensive understanding of clinical support that can be offered to children and families who bear the systemic societal mechanisms of incarceration.